Principals' Transformational Leadership in Fostering Digital Technology-Based Innovation in History Learning: A Multiple-Case Study - Wayan Satria Jaya; M. Yanuardi Zain (Jurnal Pendidikan Terapan, 2026)
This study explores how principals' transformational leadership supports digital technology-based innovation in history learning in Indonesian senior high schools. A qualitative multiple-case study was conducted in three schools in Bandung, West Java, involving 21 participants: three principals, six history teachers, and twelve students. Data were generated from semi-structured interviews, six non-participant classroom observations, and school documents collected between January and May 2024. A hybrid thematic analysis combined deductive codes derived from transformational leadership and technology-integration literature with inductive codes emerging from the data. Two researchers independently coded 20% of the dataset; the reported 87% value represents simple percent agreement, with disagreements resolved through discussion. Triangulation, member checking, peer debriefing, and an audit trail were used to strengthen trustworthiness. Four themes were identified: visionary digital leadership, stimulation of teacher creativity, cultivation of collaborative culture, and mobilization of resources and technical support. Cross-case comparison showed that the depth of innovation varied with teachers' prior competence, school resources, external support, and infrastructure. The observations also indicated that technology use was not uniformly transformative: virtual visits, primary-source analysis, and digital storytelling supported inquiry and creation, whereas gamified quizzes often remained at recall or comprehension levels. The findings therefore suggest an association between context-sensitive leadership practices and teachers' willingness and capacity to experiment, rather than a causal effect. An interpretive model is proposed to explain how leadership practices may operate through shared purpose, teacher confidence, peer learning, and reduced practical barriers under specific contextual conditions. Implications are offered for principal development and school-level implementation of the Merdeka Curriculum, while limiting transfer claims to comparable settings.